The Role of Islamic Boarding Schools in Community Economic Empowerment: A Case Study of Mertak Tombok Village, Central Lombok, Indonesia - Baiq Muniah; Habibul Umam Taqiuddin; Muhammad Yakub (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study explores the role of Islamic boarding schools (pondok pesantren) in fostering community-based economic empowerment in rural Indonesia. The research focuses on Mertak Tombok Village, Central Lombok, where the Pondok Pesantren serves as both a religious institution and an agent of socio-economic transformation. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving kiai (religious leaders), students, and local residents. The findings indicate that the pondok pesantren plays a pivotal role in developing community entrepreneurship through education, social training, and the establishment of productive enterprises such as agriculture, livestock, and handicraft cooperatives. Its leadership model—anchored in Islamic ethical values—has fostered a culture of self-reliance and collaboration among local residents. Nevertheless, challenges remain in managerial capacity, market access, and the integration of modern business practices. The study concludes that the effectiveness of pesantren-based empowerment depends on three critical factors: institutional leadership, socio-religious legitimacy, and the synergy between religious education and local economic initiatives. These findings contribute to the broader discourse on Islamic social entrepreneurship and sustainable community development in developing regions.